Maritime law - Baatz,Yvonne( editor) (Routledge., 2014)
This unique title examines in depth issues of jurisdiction, maritime law and practice from a modern perspective and highlights the importance of risk management with a view to avoiding pitfalls in litigation or arbitration and minimising exposure to liabilities